1987
DOI: 10.1002/mrd.1120170303
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry of X and Y chromosome‐bearing sperm for DNA using an improved preparation method and staining with Hoechst 33342

Abstract: A new and improved method of preparing mammalian spermatozoa for high resolution flow cytometric DNA analysis and flow sorting is described. Ejaculated or cryopreserved sperm were briefly sonicated to remove tails and then stained with Hoechst 33342. This simple procedure was found superior to more severe treatments of dimethylsulfoxide washes, fixation in 80% ethanol, and protease digestion of the sperm membranes and tails by papain. Flow cytometric DNA analyses of sperm samples subjected to varying sonicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 9 publications
0
73
0
Order By: Relevance
“…Sexed semen is now widely available in dairy industries around the world, and is nearing commercial application in several other species (Seidel, 2012). The process distinguishes X-and Y-chromosome bearing sperm by measuring differences in fluorescence following staining the sperm with a non-toxic, DNA-binding dye (Hoechst 33342) (Johnson et al, 1987). Despite reliably producing~90% gender bias (Cerchiaro et al, 2007;Borchersen and Peacock, 2009;DeJarnette et al, 2009), the fertility of the sexed semen product is compromised (Seidel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sexed semen is now widely available in dairy industries around the world, and is nearing commercial application in several other species (Seidel, 2012). The process distinguishes X-and Y-chromosome bearing sperm by measuring differences in fluorescence following staining the sperm with a non-toxic, DNA-binding dye (Hoechst 33342) (Johnson et al, 1987). Despite reliably producing~90% gender bias (Cerchiaro et al, 2007;Borchersen and Peacock, 2009;DeJarnette et al, 2009), the fertility of the sexed semen product is compromised (Seidel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…After it was demonstrated that it is not possible to differentiate sex-specific markers by physical methods, Gledhill et al (1982) published the first experiments on flow cytometry on spermatozoa, which were followed by further technical adaptations to these specific cells (Fulwyler 1977, Dean et al 1978, Stovel et al 1978, Garner et al 1983, Johnson & Pinkel 1986, Johnson et al 1987a, 1987b, Johnson & Clarke 1988. The first pre-sexed offspring using this technique were born in 1988 (Morrell et al 1988).…”
Section: Sex Sorting Of Spermatozoa By Flow Cytometrymentioning
confidence: 99%
“…Based on the excitation, spermatozoa are separated into discrete populations. In domestic animals the differences in DNA content between X and Y bearing spermatozoa ranges from 3 -4.5% (Johnson et al, 1987;Johnson, 2000). Success rate in this method has been reported to be 85 -95% (Pinkel et al, 1982;Johnson et al, 1989Johnson et al, , 2000.…”
Section: Flow Cytometrymentioning
confidence: 93%